ANALYSIS SURVIVAL THERAPY HEMODIALYSIS PADA PASIEN GAGAL GINJAL KRONIK DI RS KELAS B DR. SOSODORO DJATIKOESOEMO BOJONEGORO - MULYANI, SRI; MAFTHUKHIN, AHMAD (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2016)
ABSTRACT Hemodialysis is a short-term dialysis therapy (a few days to a few weeks) or patients with end stage renal failure (GGT) who require long-term or permanent therapy. Function hemodialysis process is removing nitrogen toxic substances from the blood and remove excess water. will be a process that is used in patients in a state of acute pain and need to replace the action of some of the functions of this ginjal.Tindakan routinely performed for chronic kidney disease (CKD) or chronic kidney disease (CKD) stage V or chronic renal failure (CRF). Characteristics of Patients undergoing hemodialysis treatment based on age, gender, type of insurance that is used and the cause of the disease itself determine the durability of a patient in therapy HD, will be performed survival analysis using Weibull regression modeling Proprtional Hazard. With the hazard function can be calculated odds ratios so that the rate known durability HD patients in therapy. Survival analysis will be obtained survival time following the Weibull distribution. Factors that affect the durability of patients undergoing HD treatment is; age, sex, type of insurance and the cause penyakit.Jenis research used non-reactive method, a method that does not invite a special reaction of the subjects studied. Researchers do not have to make direct contact or interaction with the subjects studied. Non-reactive method is also called as a method unobstrusive (Kuntoro, 2009). The experiment was conducted in a Class B RSU dr. R Sosodoro Djatikoesoemo Bojonegoro in East Java, by the time the study began on April 6, 2015 through April 11, 2015. Medical record research using data Chronic Renal Failure Patients undergoing hemodialysis therapy were recorded in a computerized format IRR report While the sample is CRF patients who are not censored the data in the time range. Class B RSU dr. R Sosodoro Djatikoesoemo since the holding facility / unit hemodialysis entire CRF patients who have been given the HD treatment in the period from 2009 to 2013 as many as 13127 of action. While research data obtained by computerized using the IRR between the months of January 2012 through March 2015 as many as 336 patients. The results showed age, type of insurance and the cause of CRF affect the durability of a CRF patients who participated HD therapy. To maintain the durability of someone who follows this therapy is to maintain the condition and the immune system of a patient CRF. In this case the role of family, friends and the people closest to the patient is very influential in a patient undergoing regular therapy. They will be the spirit of life and motivation fatherly survive with regular HD therapy. This can increase the chances of a percentage or apsien to survive longer, when compared to patients who received less support and the support of the family. The need for a comprehensive effort from all parties to CRF disease can be minimized. Neither of health care institutions, from policy makers and society in general Keywords: Analysis Survival, CKD, hemodyalisis